A UPLC-DAD-Based Bio-Screening Assay for the Evaluation of the Angiotensin Converting Enzyme Inhibitory Potential of Plant Extracts and Compounds: Pyrroquinazoline Alkaloids from Adhatoda vasica as a Case Study - Syeda Tehreem (MDPI AG, 2021)
Angiotensin converting enzyme (ACE) plays a crucial role in regulating blood pressure in the human body. Identification of potential ACE inhibitors from medicinal plants supported the idea of repurposing these medicinal plants against hypertension. A method based on ultra-performance liquid chromatography (UPLC) coupled with a diode array detector (DAD) was used for the rapid screening of plant extracts and purified compounds to determine their ACE inhibitory activity. Hippuryl-histidiyl-leucine (HHL) was used as a substrate, which is converted into hippuric acid (HA) by the action of ACE. A calibration curve of the substrate HHL was developed with the linear regression 0.999. The limits of detection and quantification of this method were found to be 0.134 and 0.4061 mM, respectively. Different parameters of ACE inhibitory assay were optimized, including concentration, incubation time and temperature. The ACE inhibition potential of Adhatoda vasica (methanolic-aqueous extract) and its isolated pyrroquinazoline alkaloids, vasicinol (1), vasicine (2) and vasicinone (3) was evaluated. Compounds 1–3 were characterized by various spectroscopic techniques. The IC50 values of vasicinol (1), vasicine (2) and vasicinone (3) were found to be 6.45, 2.60 and 13.49 mM, respectively. Molecular docking studies of compounds 1–3 were also performed. Among these compounds, vasicinol (1) binds as effectively as captopril, a standard drug of ACE inhibition.